Complete B2B online marketing - Ginty, Maura (J. Wiley & Sons, 2012)
Learn to take full advantage of search and social media for B2B marketing Business-to-business marketers have been slow to enter the online marketing arena, but now that the impact of search and social media marketing in the consumer marketplace is clearly documented, B2B marketers are ready for a complete guide to making the most of the medium. Written by experts with first-hand knowledge of the field, this book clearly explains how to leverage today's search engine marketing and social media technologies to get, nurture, and convert leads. Topics include strategy, branding, monitoring, resou.
Includes index. - Print version record
Keywords: Industrial marketing; Internet marketing; Digital media; Marketing industriel; Marketing sur Internet; Médias numériques; BUSINESS & ECONOMICS; E-Commerce; Internet Marketing; BUSINESS & ECONOMICS; Mail Order; BUSINESS & ECONOMICS; Marketing; Direct; BUSINESS & ECONOMICS; Marketing; Multilevel; BUSINESS & ECONOMICS; Marketing; Telemarketing